Legalitas Bukti Digital dalam Pembuktian Perkara Perdata di Era Siber - Rizky Alpansa; Argha Yuliarsyah (Sinergi : Jurnal Ilmiah Multidisiplin, 2026)
The rapid development of information technology has significantly transformed the civil law evidentiary system in Indonesia. The transition from conventional written documents to electronic data has raised new challenges regarding the recognition and legality of digital evidence in civil court proceedings. This study aims to examine the legal basis, implementation, and juridical as well as technical challenges of digital evidence in the proof of civil cases in the cyber era. The research adopts a normative juridical approach with a descriptive-analytical method through library research, focusing on statutory regulations, legal doctrines, and relevant literature, particularly the Law on Electronic Information and Transactions (ITE Law). The findings indicate that digital evidence has been legally recognized as valid evidence; however, its application in practice still faces several obstacles, including the risk of data manipulation, limited technical competence among law enforcement officials, and the absence of comprehensive procedural rules in civil procedural law. Therefore, regulatory reform, capacity building for legal practitioners, and the strengthening of digital forensic mechanisms are essential to ensure legal certainty, justice, and effective evidentiary processes in the digital era.   Keywords: Digital evidence, civil proof, ITE Law, cyber law, digital forensics   Abstrak Perkembangan teknologi informasi yang pesat telah membawa perubahan signifikan dalam sistem pembuktian hukum perdata di Indonesia. Peralihan dari dokumen tertulis konvensional ke data elektronik menimbulkan tantangan baru terkait pengakuan dan legalitas bukti digital dalam proses peradilan perdata. Penelitian ini bertujuan untuk mengkaji dasar hukum, penerapan, serta tantangan yuridis dan teknis penggunaan bukti digital dalam pembuktian perkara perdata di era siber. Metode penelitian yang digunakan adalah pendekatan yuridis normatif dengan metode deskriptif-analitis melalui studi kepustakaan terhadap peraturan perundang-undangan, doktrin hukum, dan literatur terkait, khususnya Undang-Undang Informasi dan Transaksi Elektronik (UU ITE). Hasil penelitian menunjukkan bahwa bukti digital telah diakui secara hukum sebagai alat bukti yang sah, namun penerapannya masih menghadapi kendala berupa potensi manipulasi data, keterbatasan kompetensi teknis aparat penegak hukum, serta belum adanya pengaturan prosedural yang komprehensif dalam hukum acara perdata. Oleh karena itu, diperlukan pembaruan regulasi, peningkatan kapasitas sumber daya manusia hukum, serta penguatan peran forensik digital guna menjamin kepastian hukum, keadilan, dan efektivitas pembuktian di era digital.   Kata Kunci: Bukti digital, pembuktian perdata, UU ITE, hukum siber, forensik digital